Review of Peripartum Hysterectomy Rates at a Tertiary Australian Hospital. Issue 4 (December 2017) - Cheng, H.C.; Pelecanos, A.; Sekar, R.
Abstract : ( Aust N Z J Obstet Gynaecol . 2016;56(6):614–618) Peripartum hysterectomy is a surgical procedure performed in the event of catastrophic postpartum hemorrhage uncontrolled by other medical and surgical therapies. In the last 3 decades, the major indication for peripartum hysterectomy has been abnormal placentation, including placenta previa, accreta, increta, or percreta. A large body of evidence suggests that a history of cesarean section (CS) is significantly associated with abnormal placentation, which is especially troubling for the antenatal population of Queensland (QLD), Australia, as the CS rate is currently higher than the national average.